Probiotic Supplementation in Mothers of Very Low Birth Weight Infants - Benor, Shira; Marom, Ronella; Tov, Amir Ben; Domany, Keren Armoni; Zaidenberg-Israeli, Galit; Dollberg, Shaul (American Journal of Perinatology, 2014)
Objective Oral probiotic supplementation reduces the risk of necrotizing enterocolitis (NEC) in preterm infants. Concerns about safety and purity of probiotic preparations have limited their use in preterm infants. The authors administered probiotic bacteria to mothers of preterm infants, thereby avoiding the risks of direct exposure of infants to probiotic bacteria.Design This prospective, randomized, double blind, placebo-controlled trial at the Tel Aviv Medical Center (June 2007–November 2009) examined the effects of maternal oral probiotic supplementation on the incidence of NEC, death, and sepsis in very low birth weight (VLBW) infants fed with maternal breast milk. Mothers were assigned to supplementation with Lactobacillus acidophilus and Bifidobacteria lactis 2 × 1010 CFU/d or to placebo starting from 1 to 3 days postpartum. The primary outcome measures were NEC, sepsis, and death.Results In total 49 mothers of 58 VLBW infants were recruited. A total of 25 infants were in the probiotic group and 33 in the placebo group. The overall incidence of Bell stage II to III NEC was 12%, with an incidence of 4% in the infants of the probiotic group and 18.2% in the placebo group (p = 0.12), respectively. Sepsis and mortality rates were similar.Conclusion Postpartum maternal supplementation with probiotic bacteria may decrease the incidence of NEC in breastfed infants.
Keywords: necrotizing enterocolitis; probiotics; preterm infant; breastfeeding; transforming growth factor; lactoferrin